Prospective study on physical activity and risk of in situ breast cancer. - Steindorf, K; Ritte, R; Tjonneland, A; Johnsen, N; Overvad, K; Ostergaard, J; Clavel-Chapelon, F; Fournier, A; Dossus, L; Lukanova, A; Chang-Claude, J; Boeing, H; et al. (2012)
BACKGROUND: Physical activity has been identified as protective factor for invasive breast cancer risk, whereas comparable studies on in situ carcinoma are rare. METHODS: The study included data from 283,827 women of the multinational European Prospective Investigation into C7ancer and Nutrition (EPIC)-cohort study. Detailed information on different types of physical activity conducted during the prior year, such as occupational, recreational, and household activity, as well as on important cofactors, was assessed at baseline. Adjusted HRs for in situ breast cancer were estimated by Cox proportional hazards models. RESULTS: During a median follow-up period of 11.7 years, 1,059 incidents of breast carcinoma in situ were identified. In crude and adjusted multivariable models, no associations were found for occupational, household, and recreational physical activity. Furthermore, total physical activity was not associated with risk of in situ breast cancer. Comparing moderately inactive, moderately active, and active participants with inactive study participants resulted in adjusted HRs of 0.99 [95% confidence interval (CI), 0.83-1.19], 0.99 (95% CI, 0.82-1.20), and 1.07 (95% CI, 0.81-1.40), respectively (P value of trend test: 0.788). No inverse associations were found in any substrata defined by age at diagnosis or body mass index (BMI) status. CONCLUSIONS: In this large prospective study, we did not find any evidence of an association between physical activity and in situ breast cancer risk. If not by chance, the contrast between our results for carcinoma in situ and the recognized inverse association for invasive breast cancer suggests that physical activity may have stronger effects on proliferation and late stage carcinogenesis.